2022
DOI: 10.3389/fmicb.2022.912536
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and mechanism-of-action of a novel synthetic antibiotic based on a dendritic system with bow-tie topology

Abstract: Over the course of the last decades, the continuous exposure of bacteria to antibiotics—at least in parts due to misprescription, misuse, and misdosing—has led to the widespread development of antimicrobial resistances. This development poses a threat to the available medication in losing their effectiveness in treating bacterial infections. On the drug development side, only minor advances have been made to bring forward novel therapeutics. In addition to increasing the efforts and approaches of tapping the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(16 citation statements)
references
References 56 publications
2
14
0
Order By: Relevance
“…BDTL100 was used in fluorescent microscopy localization studies, which revealed its accumulation at the cytoplasmic membrane of the bacterial cells leading to lipid domain formation ( Figure 3 ), and supported our previous observations pointing toward a heterogeneous affectation of the bacterial cell population. Interestingly, even though BDTL049 induces a strong cell envelope stress response in B. subtilis (as shown by previous transcriptomic analysis [ 18 ]), the sensitivity against BDTL049 of several mutant strains revealed that, except for a minor contribution of the Dlt system ( Figure 4 ), the resistance determinants which mediate the cell envelope stress response to other antibiotics are unable to mount an effective resistance response against the novel compound leaving the cell rather defenseless. Finally, the biocompatibility of BDTL049 was investigated by determining its cytotoxicity in human cell lines.…”
Section: Introductionsupporting
confidence: 53%
See 4 more Smart Citations
“…BDTL100 was used in fluorescent microscopy localization studies, which revealed its accumulation at the cytoplasmic membrane of the bacterial cells leading to lipid domain formation ( Figure 3 ), and supported our previous observations pointing toward a heterogeneous affectation of the bacterial cell population. Interestingly, even though BDTL049 induces a strong cell envelope stress response in B. subtilis (as shown by previous transcriptomic analysis [ 18 ]), the sensitivity against BDTL049 of several mutant strains revealed that, except for a minor contribution of the Dlt system ( Figure 4 ), the resistance determinants which mediate the cell envelope stress response to other antibiotics are unable to mount an effective resistance response against the novel compound leaving the cell rather defenseless. Finally, the biocompatibility of BDTL049 was investigated by determining its cytotoxicity in human cell lines.…”
Section: Introductionsupporting
confidence: 53%
“…Our previous results indicated that the cytoplasmic membrane is the primary cellular target of the novel antimicrobial compound BDTL049, which depolarizes the membrane and leads to pore formation [ 18 ]. We next aimed at visualizing the interaction of the compound with the bacterial cell in vivo.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations